The impact of pre-, pro- and synbiotics supplementation in colorectal cancer treatment: a systematic review - Moreira, Mariana Melo; Carriço, Marta; Capelas, Manuel Luís; Pimenta, Nuno; Santos, Teresa; Ganhão-Arranhado, Susana; Mäkitie, Antti; Ravasco, Paula (Frontiers in Oncology, 2024)
Introduction The effectiveness of the supplementation of prebiotics, probiotics and synbiotics as a therapeutic approach in colorectal cancer (CRC) remains unclear. The aim of this systematic review is to critically examine the current scientific evidence on the impact of modulating the microbiota, through the use of prebiotics, probiotics and synbiotics, in patients diagnosed with CRC undergoing treatment, to determine the potential therapeutic use of this approach. Methods This systematic review was made according to the PRISMA 2020 guidelines. Inclusion criteria were randomized controlled trials (RCT) comparing the impact of pre-, pro-, or synbiotic supplementation with placebo or standard care in patients with CRC undergoing treatment. Exclusion criteria were non-human studies, non-RCTs, and studies in languages other than English or Portuguese. Six databases were consulted, namely, Cochrane Library, Pubmed, Scopus, Cinahl, MedicLatina and Web of Science until May of 2023. RAYYAN software was used to manage the search results and risk of bias was assessed according to the guidelines of the Cochrane Collaboration using the Rob 2.0 tool. Results Twenty-four RCTs met the inclusion criteria and were included in this review. Administration of pre-, pro-, or synbiotics improved surgical outcomes such as the incidence of infectious and non-infectious postoperative complications, return to normal gut function, hospital length of stay, and antibiotic usage. The supplementation of these microorganisms also alleviated some symptoms from chemotherapy and radiotherapy, mainly diarrhea. Evidence on the best approach in terms of types of strains, dosage and duration of intervention is still scarce. Conclusions Pre-, pro-, and synbiotics supplementation appears to be a beneficial therapeutic approach in CRC treatment to improve surgical outcomes and to alleviate side-effects such as treatment toxicity. More RCTs with larger sample sizes and less heterogeneity are needed to confirm these potential benefits and to determine the best strains, dosage, and duration of administration in each situation. Systematic review registration https://www.crd.york.ac.uk/prospero, identifier CRD42023413958.